Central Nervous System Complications in Children Receiving Chemotherapy or Hematopoietic Stem Cell Transplantation - Cordelli, Duccio Maria; Masetti, Riccardo; Zama, Daniele; Toni, Francesco; Castelli, Ilaria; Ricci, Emilia; Franzoni, Emilio; Pession, Andrea (Frontiers in Pediatrics, 2017)
Therapy-related neurotoxicity greatly affects possibility of survival and quality of life of pediatric patients treated for cancer. Central nervous system (CNS) involvement is heterogeneous, varying from very mild and transient symptoms to extremely severe and debilitating, or even lethal syndromes. In this review, we will discuss the broad scenario of CNS complications and toxicities occurring during the treatment of pediatric patients receiving both chemotherapies and hematopoietic stem cell transplantation. Different types of complications are reviewed ranging from therapy related to cerebrovascular with a specific focus on neuroradiologic and clinical features.